2017
DOI: 10.1016/j.fishres.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Otolith shape and size: The importance of age when determining indices for fish-stock separation

Abstract: Stock-separation of highly mobile Clupeids (sprat -Sprattus sprattus and herringClupea harengus) using otolith morphometrics was explored. Analysis focused on three stock discrimination problems with the aim of reassigning individual otoliths to source populations using experiments undertaken using a machine learning environment known as WEKA (Waikato Environment for Knowledge Analysis). Six feature sets encoding combinations of size and shape together with nine learning algorithms were explored. To assess sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…Moreover, fish size should always be accounted for because it affects otolith shape even in age-0 fish. Our results are consistent with Mapp et al (2017), who showed that including size information increases the power of stock discrimination based on juvenile otolith shape. The formfactor decreased with increasing size in both nursery grounds and during both sampling years, while ellipticity increased in the Belgian nursery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, fish size should always be accounted for because it affects otolith shape even in age-0 fish. Our results are consistent with Mapp et al (2017), who showed that including size information increases the power of stock discrimination based on juvenile otolith shape. The formfactor decreased with increasing size in both nursery grounds and during both sampling years, while ellipticity increased in the Belgian nursery.…”
Section: Discussionsupporting
confidence: 93%
“…Thus other factors, such as genetic background, spawning location and dispersal may also be important in influencing otolith shape (Cardinale et al, 2004;Capoccioni et al, 2011;Lombarte et al, 2003;Mapp et al, 2017). This observation is supported by the similar levels of variation in otolith shape between nursery grounds and between the two successive sampling years.…”
Section: Small Differences Between Nursery Groundsmentioning
confidence: 63%
“…The study of relationship between otolith size and fish size varied according to the distribution region, the stock and sexes (Sparre et al, 1989;Campana and Casselman, 1993;Reichenbacher et al, 2009;Aneesh et al, 2017), also the change of ontogenetic in the life span or history (Hare and Cowen, 1995). The present work was confirmed with other studies that investigated the correlation between fish length and otolith size (Mahé et al, 2014;Mahé et al, 2016;Mehanna et al, 2016;Jawad, et al, 2017;Mapp 2017;Mahé et al, 2018;Osman et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…However, the right and left otoliths may not provide the same results of prey fish length estimates (Harvey et al 2000;Waessle et al 2003;Kumar et al 2012). The morphological and meristic characteristics of fish and their hard body parts have been shown as useful in stock identification studies (Kumar et al 2017;Bostanci et al 2017;Mapp et al 2017). Otoliths are useful because their growth is related to increase in fish size and generally follow an allometric increase in dimensions (Chilton and Beamish 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The stock concept is one of the most fundamental in fishery management. The morphological characteristics of fish otoliths have been taken into account in recent years in stock separation studies (Tuset et al 2003;Zengin et al 2015;Renán et al 2016;Bostanci et al 2017;Kumar et al 2017;Mapp et al 2017). The difference in otolith measurement values among the populations will contribute to the stock sorting studies to be performed thereafter.…”
Section: Introductionmentioning
confidence: 99%